2012
DOI: 10.1097/gme.0b013e318227304b
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in the association between carotid plaque and aortic and coronary artery calcification among women transitioning through menopause

Abstract: Background Carotid atherosclerosis is a marker for atherosclerotic disease in other vascular beds; however, racial differences in this association have not been fully examined. The purpose of this report is to evaluate racial differences in the relationship between carotid plaque and calcification in the aorta and coronary arteries among women transitioning the menopause. Methods 540 African American and White women with a median age of 50 years were evaluated from the Study of Women’s Health Across the Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
(39 reference statements)
2
7
0
Order By: Relevance
“…The power to evaluate associations with incident events, especially when stratified by prior randomization to CEE‐Alone versus placebo, is limited by the low rates of CHD, CVD, and CVD mortality. These low event rates are related to the very low prevalence of CAC (ie, 54% of the women had CAC=0 and 62% had CAC <10), consistent with other studies showing much lower prevalence of coronary calcification in women than men, and very low incidence of CHD and CVD in both men and women with low CAC scores 7, 20. Finally, while presence and severity of CAC is strongly associated with the overall atherosclerotic plaque burden, it does not quantify noncalcified plaque, and may also represent inflammation or other determinants of tissue calcification 21, 22, 23.…”
Section: Discussionsupporting
confidence: 89%
“…The power to evaluate associations with incident events, especially when stratified by prior randomization to CEE‐Alone versus placebo, is limited by the low rates of CHD, CVD, and CVD mortality. These low event rates are related to the very low prevalence of CAC (ie, 54% of the women had CAC=0 and 62% had CAC <10), consistent with other studies showing much lower prevalence of coronary calcification in women than men, and very low incidence of CHD and CVD in both men and women with low CAC scores 7, 20. Finally, while presence and severity of CAC is strongly associated with the overall atherosclerotic plaque burden, it does not quantify noncalcified plaque, and may also represent inflammation or other determinants of tissue calcification 21, 22, 23.…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence of plaque among pre-and postmenopausal women included in the HWS was 25% and 57%, respectively [23,24]. Woodard et al [25], in a study that included African-American and white women during the menopause transition, found a lower prevalence of plaque: 15.14%. Although the median age was 50, only 30.7% of participants were postmenopausal [25].…”
Section: Discussionmentioning
confidence: 97%
“…Woodard et al [25], in a study that included African-American and white women during the menopause transition, found a lower prevalence of plaque: 15.14%. Although the median age was 50, only 30.7% of participants were postmenopausal [25]. Recently, Lambrinoudaki et al [9], in a study that included 120 postmenopausal women (mean age 53 years), showed a combined IMT (median total measurements of bilateral carotids) of 0.724 (±0.127), and presence of plaque in 28% of participants.…”
Section: Discussionmentioning
confidence: 97%
“…The study by Lee et al was in Caucasians [14], whereas the study reported here is in Asians. In some previous studies ethnic differences in the prevalence and correlates of carotid atherosclerosis were observed [3031]. Woodard et al demonstrated that the presence of carotid plaques was associated with aortic and coronary artery calcification in White women, but not African-American women [31].…”
Section: Discussionmentioning
confidence: 99%
“…In some previous studies ethnic differences in the prevalence and correlates of carotid atherosclerosis were observed [3031]. Woodard et al demonstrated that the presence of carotid plaques was associated with aortic and coronary artery calcification in White women, but not African-American women [31]. Another study compared the relationship between coronary calcium and carotid atherosclerosis in four different ethnic groups of White, Black, Hispanic, and Chinese [32].…”
Section: Discussionmentioning
confidence: 99%